Pengaruh Suku Bunga, Harga Emas, dan Harga Minyak Dunia Terhadap Indeks Harga Saham Gabungan (IHSG) Dengan Profitabilitas Sebagai Variabel Moderating - Wini Oktaviani (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2026)
This study aims to determine the effect of Interest Rates, Gold Prices and World Oil Prices on the Jakarta Composite Index (JCI) with Profitability as a Moderating Variable in LQ45 companies listed on the Indonesia Stock Exchange (IDX) in 2020-2024 using the Purpose Sampling method. The analytical method in this study is panel data regression analysis. The results of this study determine that Interest rates have a positive and significant effect on the JCI. Gold prices have a positive and significant effect on the JCI. World oil prices have a positive and significant effect on the JCI. Interest rates are moderated by Profitability and have a positive but insignificant effect on the JCI. Gold prices are moderated by Profitability and have a positive but insignificant effect on the JCI. World oil prices are moderated by Profitability and have a positive but insignificant effect on the JCI.